Assessment of the impact of health insurance medical advisors’ involvement on partograph utilization in the context of free maternity care: an analytical cross-sectional study conducted in maternity units of the Lemba Health Zone, Democratic Republic of the Congo - Bardy Mense Mbey; T. Bukele Kekemb; D. Ngo-Bebe; P. Nkolamoyo Musungula; A. Mpula Nsongo; C. Kalengo Nsomue (African Scientific Reports, 2026)
The quality of partograph documentation is a key component of obstetric care safety. In the Democratic Republic of the Congo (DRC), implementation of the free maternity care policy was accompanied by an obstetric record audit mechanism conducted by medical advisors. Based on a clinical audit, this comparative study used a checklist adapted from the French National Agency for Accreditation and Evaluation in Health (ANAES) framework to assess changes in partograph documentation compliance before and after introduction of the free maternity care policy in twelve maternity units of the Lemba Health Zone. A total of 844 partographs were selected through systematic sampling across two comparable periods. Comparisons were performed using Pearson's chi-square test or Fisher's exact test, with statistical significance set at p < 0.05. The median age of parturient women was 28 years (interquartile range [IQR]: 8 years; range: 16--44 years). The number of criteria achieving a compliance rate of at least 75% increased from 23 to 31 out of the 34 assessed criteria. The largest improvements were observed in the documentation of laboratory examinations (36.0% vs. 82.0%), integration of the partograph into the medical record (36.0% vs. 77.7%), description of amniotic fluid characteristics (66.0% vs. 96.2%), and monitoring of women during the immediate postpartum period (39.0% vs. 86.0%) (p < 0.001 for each comparison). However, documentation of fetal position (57.6%) and level of the presenting part (58.1%) remained below the target threshold. Overall, compliance improved between the two periods, although some technical obstetric parameters remained insufficiently documented. These findings highlight the need to strengthen healthcare providers' competencies in clinical monitoring and obstetric documentation.